Mykola Stepanenko: PERIPHRASTIC INTERRELATIONS OF THE CHORONYM RUSSIA IN THE PUBLICISTIC AND POLITICAL DISCOURSE: THE STRUCTURE, SEMANTICS AND AXIOLOGY - Stepanenko, Mykola (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. The article embraces the in-depth investigation of periphrastic inversions, which characterise the choronym Russia from the various standpoints; the latter has been intensely used in the up-to-date publicistic-political discourse. Purpose. The goal of the research is to identify via the periphrastic sphere’s prism diverse nomination criteria of semantic differentiation and axiological potential of the choronym Russia in the comprehensive publicistic-political discourse. Method. The descriptive method, method of distribution and method of concept analysis were implemented successfully. Results. In fact, periphrases appear due to extralingual factors (among them one can find historical, cultural, social, economic, political patterns, etc.). Their creation is mainly determined by the necessity to reveal vividly manifested positive or negative evaluation of a certain denotation. These data have its base on statistics, got under the terms of continuous sample, highlighting peculiarities of the formal-grammatical structure of descriptive patterns. As a results, periphrases-collocations (simple coordinate and subordinate, complex subordinate, co-ordinate and combined subordinate-co-ordinate) as well as periphrases-complex sentences were logically differentiated. The thorough attention was paid to periphrastic paradigms’ semantic typology interpretation; their constituents may explicate specific semantics and some peculiar connotative meaning. Totally, the derivative nominations form the whole idea of the denotatum Russia in all its complicacy. Finally, it was set that periphrastic inversions undergo definite nomination criterion as a base of production. The periphrastic corpus incorporates such units as “periods of formation and evolution of Russia”, “bordering of Ukraine and Russia”, “up-to-date relations between Ukraine and Russia”, “head of the state”, “state symbol – emblem in the form of the golden double-headed eagle”, “obscene cheer about the president of the Russian Federation Volodymyr Putin with the repeating syllable -la”, “form of governing in the modern Russia”, “external functions of Russia as a state”, “authority and status of the Russian Federation in the global dimension”, “militarization”, “non-compliance of the own legislation, ignoring the internal law”, “forced expulsion of other ethnicities or some unwanted groups of citizens or certain people from the territory” ascertained and profoundly analysed. The focus of the research is on the process when the presented above derivative nomination constitutes specific semantics based on determined (mainly nouns with a distinct connotation) and determining (mostly adjectives with secretory, social, evaluation, and negative evaluation) units. Such semantic-syntagmatic analysis also embraces semasiological procedures. It was the axiological potential of periphrases to be thoroughly examined. Originality. In consequence, it was established that their pejorative connotation significantly dominates over meliorative, being provoked by extralingual factors, particularly by special features of internal and external activity of Russia as independent state and participant of the modern globe. Likewise, there is an exceptional complexity of the up-to-date Ukrainian-Russian relations. Conclusions. The choronym Russia sets a sufficiently branched spectrum of periphrastic interconnections, functioning as one of the crucial semantic-axiological centres of the publicistic-political discourse.